An Empirical Study on the Exchange Rate Volatility of Shanghai Cooperation Organization Countries Based on Computer Software Analysis. Issue 2 (May 2021) - Huang, Xiaodong
Abstract: With the rapid development of our economy, the market of economic exchange rates between our country and other countries has also fluctuated. This paper analyzes the volatility of exchange rates among members of the Shanghai Cooperation Organization. The result shows that the economic volatility and exchange rate volatility among its members have strengthened gradually, and the courseware Shanghai Cooperation Organization has been developing steadily.